The Consensus on Economic Policy in an Emerging Economy: Evidence from the Cracow University of Economics - Janus, Jakub; Burda, Adrian; Pokrywka, Łukasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Both the recent financial crisis and the global recession vividly demonstrated the deficiencies in the economic theory. The main challenges faced by economists are to determine the economic role the state is to play and the particular features of its economic policy. The authors set out to determine the level of consensus on the above subjects among faculty members employed at the Cracow University of Economics (CUE). The research has been narrowed down to issues in the economic policies of emerging market economies (e.g. Poland). A survey containing 30 propositions was conducted in May and June 2011 in six departments of the CUE and covered fiscal, monetary, social, exchange-rate, trade, and regulatory policies. Analysis of the data collected enabled the authors to evaluate the level of consensus in each area and consequently, in a comprehensive manner, to discuss the relative convergence of opinions. The authors concluded that there is generally a significant level of consensus among participants, but the on-going redefinition of views on macroeconomic policies should also be noted.